1997
DOI: 10.13031/2013.21391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Watershed Subdivision on Simulation Runoff and Fine Sediment Yield

Abstract: The objective of this study was to establish the subwatershed size dependency of the Soil and Water Analysis Tool (SWAT) erosion model to adequately simulate annual runoff and fine sediment (< 0.063 mm) from the 21.3 km 2 Goodwin Creek Watershed (GCW). Results of the GCW application show that runoff volume is not appreciably affected by the number and size of subwatersheds. However, an upper limit to subwatershed size is required to adequately simulate fine sediment yield produced from upland sources. Decreasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 7 publications
11
82
1
Order By: Relevance
“…However, the gap in accuracy between the two approaches decreased with increasing numbers of subwatersheds. Bingner et al (1997) report that the number of simulated subwatersheds affected predicted sediment yield and suggested that sensitivity analyses should be performed to determine the appropriate level of subwatersheds. Jha et al (2004a) found that SWAT sediment and nitrate predictions were sensitive to variations in both HRUs and subwatersheds but mineral P estimates were not.…”
Section: Hru and Subwatershed Delineation Effectsmentioning
confidence: 99%
“…However, the gap in accuracy between the two approaches decreased with increasing numbers of subwatersheds. Bingner et al (1997) report that the number of simulated subwatersheds affected predicted sediment yield and suggested that sensitivity analyses should be performed to determine the appropriate level of subwatersheds. Jha et al (2004a) found that SWAT sediment and nitrate predictions were sensitive to variations in both HRUs and subwatersheds but mineral P estimates were not.…”
Section: Hru and Subwatershed Delineation Effectsmentioning
confidence: 99%
“…Applications of SWAT in watersheds in humid regions have been abundantly published in the literature (e.g., Srinivasan et al, 1993;Srinivasan and Arnold, 1994;Cho et al, 1995;Bingner et al, 1997;Arnold et al, 1999;Santhi et al, 2001;Kaur et al, 2003). However, applications of SWAT in dry environments are still relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…An obvious approach is to divide the watershed into its natural sub-watersheds, thus preserving the watershed's natural boundaries, flow-paths and channels for realistic water routing [23][24][25][26][27][28][29]. The concepts of critical source area [30][31][32][33][34][35][36], threshold drainage area [37] and aggregated simulation area [38] have also been used to delineate sub-watersheds within semi-distributed models.…”
Section: Overview Of Schematization and Parameterization Approaches Imentioning
confidence: 99%